P305 Challenges Of Developing Clinical Practice Guidelines (Cpg) For Pediatric Cancer In Colombia. (15th August 2013) - Linares, A; Torres, M; Pardo, R
Abstract : Background: WHO estimates for the year 2013 that approximately 12 million deaths will be attributed to cancer. In developing countries, 180.000 childhood cancer cases occur every year. Context: the need to standardise the management of childhood haematological cancers and reach the same survival rates in developed and developing countries require the elaboration of clinical practice guidelines (CPG) in Colombia. The overall survival for acute lymphoid leukaemia is around 50% while in other countries is near 80%. description of best practice: the ministry of health assigned the development of a CPG of childhood acute leukemias and lymphomas. The guideline development group (GDG) had to face some challenges due to the amount/quality of evidence and the patients' point of view. lessons for guideline developers, adaptors, implementers, and/or users: during the formulation of the recommendations, not only effectiveness is a critical outcome but treatment toxicity and adverse effects such as secondary neoplasies need to be evaluated. In order to identify relevant information of safety, the GDG had to include observational studies which brought up some challenges. The GDG developed a qualitative exercise for the identification of patients' point of view that were weighted in equal manner with the risk and benefits of the interventions. Once the guideline was finished, the recommendations were driven towards patient safety and the implementation implied to make changes in public policies, improve the access to continuous therapy, proper diagnosis, modifications in resources assignment and work around the available treatment so the overall survival can reach international standards.